Hookworm infections among Aboriginal (Orang Asli) Primary School Children at a Semi Urban School in Kuala Kubu Bharu, Selangor - Noradilah SA; Mohamed Kamel AG; Robiah M; Fadlul Azim Fauzi Mansur (Universiti Sains Islam Malaysia, 2024)
Buletin SK 4(2)(2020): 60-62